Analisis Jabatan dan Manajemen Karir: Strategi Pengembangan Sumber Daya Manusia (SDM) Yang Terpadu - Mardiyah; Hotimah, Husnul; Ekaputri, Dinti; Mujtahidah, Imamah (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2025)
Job analysis and career management are two concepts that are closely related to each other in the world of human resource management (HR). Both have an important role in ensuring organizational effectiveness and employee satisfaction. The integration of job analysis in management not only improves individual and team performance, but also contributes to the achievement of the organization's strategic goals. By understanding the background and importance of job analysis, organizations can be better prepared to face future challenges and create a productive and innovative work environment. The research was carried out using a literature study or literature study type of research. This type of research can be used by collecting references consisting of several previous studies which are then combined to draw conclusions. A human resource development strategy is basically a series of decisions and actions used to create and implement plans to improve human resource capabilities. Job analysis and human resource (HR) planning are closely related because both are the basis for making strategic decisions in managing human resources. There is collaboration in the implementation of career development activities, of course very much determined by the individual and the role of the personnel department or organization.